Usefulness of warning signs in the management of dengue patients - Castro Peraza, Osvaldo; MartÃnez Torres, Eric; MartÃnez RodrÃguez, Alina; González Rubio, Daniel; Guzman Tirado, MarÃa Guadalupe (Revista Cubana de Medicina Tropical, 2022)
Introduction: The dengue case classifications proposed by World Health Organization (WHO, 2009) include warning signs (WS) for recognizing early progression of disease toward the critical phase. Objective: To analyze the usefulness WS and challenges of the 2009 WHO dengue case classification in preventing and managing severe dengue cases. Methods: Data from 1439 adult patients diagnosed as dengue cases (2001-2002, 2006, 2012) at the Pedro Kourí Institute Hospital, in Havana Cuba, was revised. The WS were described and their predictive utility was considered in preventing shock in these patients with the use of crystalloids by calculating the sensitivity, specificity and positive / negative predictive values using both the 1997 and 2009 WHO dengue case classifications. Results: Plasma-leakage with shock was the main clinical form of severe dengue (95.3%). All severe cases due to plasma leakage had WS. The most frequent WS were mucosal bleeding (926 cases; 64.4%), frequent vomiting (361; 39.0%), abdominal pain or tenderness (404; 35.5%) and prostration (408; 28.4%). Mucosal bleeding and abdominal pain were good predictors of severity, appearing one day before shock. More than 75% of patients without WS there were not severe dengue. Most patients with warning signs were managed correctly and had an uneventful recovery. Conclusions: Identifying the WS recommended by WHO 2009 classification for crystalloid intravenous fluid treatment was crucial for the successful outcome of dengue cases.